Antimicrobial Activity of Sonneratia ovata Backer - Laili Khumaidah; Adi Setyo Purnomo; Sri Fatmawati (HAYATI Journal of Biosciences, 2019)
Sonneratia, a genus of mangroves from family Lythraceae, is reported for number of high biological activity including antimicrobial. Sonneratia ovata Backer is one of the species which traditionally used by Indonesian people for the treatment of some diseases. In this research, the investigation about biological activity of S. ovata Backer as anti-microbial has been performed. The methanol extract of S. ovata Backer is highly potential as antimicrobial against gram positive bacteria, S. aureus, with IC50 value of 7.7 μg/ml which is higher than of Ampicillin as positive control with IC50 value of 37.8 μg/ml. Furthermore, stigmasterol one of the major compound of S. ovata Backer has been isolated from the methanol extract of the stem bark of S. ovata Backer. Therefore, S. ovata Backer is proven to have high activity as antimicrobial, and highly potential to be a new source of antimicrobial agent.